IMPLEMENTASI PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 28 TAHUN 2012 TENTANG KEARSIPAN PADA LEMBAGA LAYANAN PENDIDIKAN TINGGI WILAYAH II - Sunarto Sunarto (MAP Program Pascasarjana Universitas Sjakhyakirti, 2021)
when necessary so that the office can provide effective services. Archives are needed in administration because archives are the center of memory for every activity in an office. Without archives, it is impossible for an archivist to remember all records and documents completely. The data analysis technique in this study uses inductive logic. The analysis will move from something specific or specific, namely those obtained in the field, towards a finding that is general in nature and can draw a conclusion. The results show that the implementation of the Republic of Indonesia Government Regulation Number 28 of 2012 concerning Archives at the Region II Higher Education Service Institution has not been carried out properly, the archives are still partially stored, this is due to insufficient human resources and a special archive room is not yet available